A Note on Weighted Estimates for the Schrödinger Operator - Ruiz, Alberto; Bennett, Jonathan M.; Carbery, Anthony; Vilela, M. Cruz; Barceló, Juan A. (Revista Matemática Complutense, 2008)
We study two problems closely related to each other. The first one is concerned with some smoothing weighted estimates with weights in a certain Morrey- Campanato spaces, for the solution of the free Schrödinger equation. The second one is a weighed trace inequality.